Influence of coaching efficacy and coaching motivation on coaching satisfaction among Malaysian coaches / Nur Atikah Mohamed Kassim - Mohamed Kassim, Nur Atikah (2019)
Coaches have the responsibility in guiding the athletes to be successful in their sports performance by helping in improving their skills. Hence to help athletes’ performances, coaches need to have certain specific abilities such as coaching efficacy, coaching motivation, and coaching satisfaction. Therefore, the purpose of this study was to determine the influence of coaching efficacy and coaching motivation, on coaching satisfaction among Malaysian coaches. This study also aimed to determine whether coaching motivation mediates the relationship between coaching efficacy and coaching satisfaction. A total of 323 coaches who coached in Sukan Malaysia (SUKMA 2016) were selected through purposive sampling participated in this study.